2022
DOI: 10.1002/jmv.28371
|View full text |Cite
|
Sign up to set email alerts
|

SFTS bunyavirus NSs protein sequestrates mTOR into inclusion bodies and deregulates mTOR‐ULK1 signaling, provoking pro‐viral autophagy

Abstract: Autophagy is emerging as a critical player in host defense against diverse infections, in addition to its conserved function to maintain cellular homeostasis. Strikingly, some pathogens have evolved strategies to evade, subvert or exploit different steps of the autophagy pathway for their lifecycles. Here, we present a new viral mechanism of manipulating autophagy for its own benefit with severe fever with thrombocytopenia syndrome bunyavirus (SFTSV, an emerging high‐pathogenic virus) as a model. SFTSV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(248 reference statements)
1
8
0
Order By: Relevance
“…Previous studies reported that SFTSV infection induces autophagic processes in HeLa cells [53] and inhibits autophagic degradation in Vero cells [54]. LC3 accumulation, which is required for autophagosome formation, was observed in both studies [53,54]. In this study, increased levels of LC3B were observed, which suggested the occurrence of autophagy in the platelets of SFTS patients.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies reported that SFTSV infection induces autophagic processes in HeLa cells [53] and inhibits autophagic degradation in Vero cells [54]. LC3 accumulation, which is required for autophagosome formation, was observed in both studies [53,54]. In this study, increased levels of LC3B were observed, which suggested the occurrence of autophagy in the platelets of SFTS patients.…”
Section: Discussionsupporting
confidence: 67%
“…In SFTS patients, although the increase in platelet MLKL levels was not as great as the levels of pyroptosis and apoptosis biomarkers, their increase still indicated a role of necroptosis in thrombocytopenia. Previous studies reported that SFTSV infection induces autophagic processes in HeLa cells [53] and inhibits autophagic degradation in Vero cells [54]. LC3 accumulation, which is required for autophagosome formation, was observed in both studies [53,54].…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, viral replication levels were affected by the NS mutants, which was verified with quantitative real-time polymerase chain reaction (qRT-PCR) and the 50% fluorescent antibody infectious dose (FAID 50 ) [ 16 ]. It has been reported that NSs and NP are involved in autophagosome formation and replication [ 12 , 17 , 18 ]. Therefore, we further explored whether these viral proteins alter LC3 and p62 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mTOR-dependent signaling is crucial in regulating autophagy. Previous studies revealed that SFTSV infection decreased the phosphorylation of mTOR and the downstream effector unc-51-like kinase 1 (ULK1) [ 17 , 18 ]. Therefore, we also examined the changes in regulatory factors according to the presence or absence of viral proteins and their binding.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the NSs protein in WUXV remains elusive. Nonetheless, the NSs protein is widely recognized as a pivotal virulence determinant among phleboviruses, exerting significant influence on the evasion strategies employed by the virus to counteract the host’s innate immune response [ 22 , 44 ]. Among the mutation sites mentioned above, only two (M-312 and M-340) in the M segment exhibited both amino acid mutations and positive selection pressure.…”
Section: Discussionmentioning
confidence: 99%